Evolving customized non-polysaccharidase Mixture for effective utilization of sorghum Stover and groundnut haulm - M.I. Yancy; C. Valli; V.Balakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was undertaken with an objective of evolving substrate specific customized non-starch polysaccharidase mixture for effective utilization of sorghum stover and groundnut haulm. Enzyme activity (IU/g) assay revealed that the activity of cellulose, xylanase and pectinase were 1368.33±23.30, 2294.16±65.17 and 930.83±52.22 respectively. All enzymes were found to have associate activity of other enzymes. An invitro trial was conducted to identify the concentration range of individual non-starch polysaccharidase enzymes required for inclusion to sorghum stover and groundnut haulm for maximum hydrolysis. A second invitro trial was conducted to identify the precise concentration of individual non-starch polysaccharidase enzymes required for inclusion to sorghum stover and groundnut haulm for maximum hydrolysis. The third in vitro trial was conducted to optimize the concentration of non-starch polysaccharidase mixture for inclusion to sorghum stover and groundnut haulm for maximum hydrolysis. The efficacy of customized non-starch polysaccharidase mixture was further evaluated at three levels (viz the selected level, 10% higher than selected level and 10% lower than the selected level)to arrive at their optimal level of inclusion separately for sorghum stover and groundnut haulm.